Microfluidic fabrication of microparticles for biomedical applications. (12th July 2018) - Li, Wen; Zhang, Liyuan; Ge, Xuehui; Xu, Biyi; Zhang, Weixia; Qu, Liangliang; Choi, Chang-Hyung; Xu, Jianhong; Zhang, Afang; Lee, Hyomin; Weitz, David A.
Abstract : This review summarizes microparticles produced by droplet microfluidics and their applications in biomedical fields. Abstract : Droplet microfluidics offers exquisite control over the flows of multiple fluids in microscale, enabling fabrication of advanced microparticles with precisely tunable structures and compositions in a high throughput manner. The combination of these remarkable features with proper materials and fabrication methods has enabled high efficiency, direct encapsulation of actives in microparticles whose features and functionalities can be well controlled. These microparticles have great potential in a wide range of bio-related applications including drug delivery, cell-laden matrices, biosensors and even as artificial cells. In this review, we briefly summarize the materials, fabrication methods, and microparticle structures produced with droplet microfluidics. We also provide a comprehensive overview of their recent uses in biomedical applications. Finally, we discuss the existing challenges and perspectives to promote the future development of these engineered microparticles.